EP734 The value of omentectomy for surgical staging of borderline ovarian tumors. (1st November 2019) - Maria, S; Mimoun, C; Marchand, E; Mezzadri, M; Place, V; Cornelis, F; Huchon, C; Perrin, M; Benifla, J-L
Abstract : Introduction/Background: Management of borderline ovarian tumors (BOTs) is surgical. The complete surgical staging includes exploration of peritoneal cavity and systematic peritoneal washing, omentectomy and random peritoneal biopsies. The systematic omentectomy is controversial in BOTs. The purpose of the study was to identify risk factors associated with omental involvement. Methodology: This retrospective bicentric study included 70 patients with BOTs from December 2001 to April 2018. All patients underwent omentectomy (infracolic, infragastric or large biopsy) and pathological analysis of omentectomy was recorded in all cases. Results: Sixty three patients (90%) were diagnosed at International Federation of Gynecology and Obstetrics (FIGO) stage I. Histologic subtypes were serous (62.9%), mucinous (32.9%) and endometrioid type (4.3%). Macroscopic disease in the omentum was suspected in one case, with a normal histological assessment. Occult omental disease was found in 6 cases (8.6%). In univariate analysis, omental involvement was significatively associated with presumed advanced FIGO stage (> IIB) (p=0.002), Cancer Antigen 125 (>100) (p=0.001), abnormal exploration of peritoneal cavity (p=0.003), peritoneal implants (p=0.00) and microinvasion (p=0.001). In multivariate analysis, omental involvement was significatively associated with presumed advanced FIGO stage (> IIB) and stromal microinvasion (p=0.015 and p=0.012, respectively). Conclusion: In our study, microinvasion is an independent risk factor for omental involvement. Furthermore, patients with presumed advanced stage BOTs may benefit from systematic omental staging. Disclosure: Nothing to disclose.